2010
DOI: 10.1111/j.1939-165x.2009.00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of peripheral blood neutrophil function in tumor‐bearing dogs

Abstract: Background: Peripheral blood neutrophils of untreated human cancer patients have been shown to have normal, increased, and decreased phagocytic activity, killing capacity, and/or oxidative burst activities. Objectives: The objectives of this study were to evaluate oxidative burst and phagocytic activities of peripheral blood neutrophils from tumor‐bearing dogs before therapy and compare them with neutrophil function of healthy control dogs. Methods: Heparinized whole blood was obtained from dogs with high‐g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 13 publications
1
22
1
Order By: Relevance
“…As the CHSPCs have been further characterized, we have found that the human markers do not fully correlate with the canine cell subtypes. Interestingly, recent studies utilizing flow cytometry have shown differences in myeloid and lymphoid cells in the diagnosis and successful treatment of canine malignancies (LeBlanc et al, 2010; Tominaga et al, 2010; Comazzi et al, 2011). In a preliminary flow cytometry assessment of therapy with the anti-angiogenic agent ABT-510, there was no significant change in circulating endothelial cells in 10 dogs that experienced early disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…As the CHSPCs have been further characterized, we have found that the human markers do not fully correlate with the canine cell subtypes. Interestingly, recent studies utilizing flow cytometry have shown differences in myeloid and lymphoid cells in the diagnosis and successful treatment of canine malignancies (LeBlanc et al, 2010; Tominaga et al, 2010; Comazzi et al, 2011). In a preliminary flow cytometry assessment of therapy with the anti-angiogenic agent ABT-510, there was no significant change in circulating endothelial cells in 10 dogs that experienced early disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Additional exclusion criteria were: previously diagnosed immune system disorder (such as immune mediated disease), history of inflammatory disease within 3 months of presentation, non‐measurable tumour burden or breeds with known congenital neutrophil dysfunction disorders (Brittany Spaniel, Weimaraner, Foxhound, Pointer, Irish Setter, Doberman). Dogs with neoplasia were divided into the soft tissue sarcoma (STSA) group or the general neoplasia group, because STSA has been specifically associated with cancer‐induced immunodysfunction in dogs . Dogs in the control group were deemed healthy based on history, physical examination and complete blood count.…”
Section: Methodsmentioning
confidence: 99%
“…Dogs with spontaneously occurring cancer often have cancer‐associated immunosuppression that is similar to cancer‐associated immunosuppression in humans . Administration of immunosuppressive medications such as chemotherapy exacerbates cancer‐associated immunosuppression, further increasing the risk of sepsis .…”
Section: Introductionmentioning
confidence: 99%
“…Propidium iodide was added to stain DNA; this allowed exclusion of aggregation artifacts of bacteria or dead cells during flow cytometry. Oxidative burst activity was also determined using a commercially available test kit (Phagoburst ® , Orpegen Pharma, Heidelberg, Germany) validated for use with canine blood (LeBlanc et al, 2010) according to manufacturer instructions. Heparinized whole blood was incubated with various stimuli (unlabeled opsonized E. coli LE392, PMA, or control solution).…”
Section: Phagocytosis and Oxidative Burstmentioning
confidence: 99%
“…Following incubation with resveratrol or control, PMN phagocytic and oxidative burst capacity were determined. Canine PMN phagocytic ability was determined using a commercially available test kit (Phagotest ® , Orpegen Pharma, Heidelberg, Germany) previously validated for dogs (LeBlanc et al, 2010) according to manufacturer instructions. Heparinized whole blood was incubated with FITC-labeled opsonized E. coli strain LE392 for 10 min in a 37 • C water bath to stimulate phagocytosis by white blood cells; negative control samples were those incubated without bacteria.…”
Section: Phagocytosis and Oxidative Burstmentioning
confidence: 99%